Melanogenic Inhibitory Effects of Sesamum indicum Phytocompounds Towards CDK 2, c-KIT, and BRAF. - Shetty Manasa Jagadish (International Journal of Bioinformatics and Computational Biology, 2023)
Objective: Melanoma is thought to be the fifth most frequent cancer in the US population, despite cancer being the most common cause of death in the globe. BRAF, CDK2, and c-KIT proteins are regarded as potential therapeutic agents since mutations in these proteins are the primary cause of melanoma. For the investigation of their pharmacological properties and therapeutic activities against the target proteins, Sesamum indicum L. and its phytocompounds were chosen. Additionally, the comparison study of phytocompounds utilized the two common medications Dacarbazine and Dabrafenib mesylate. Methods: In this investigation, target proteins were downloaded from the PDB and docked in PyRx with 50 phytocompounds of sesame and 2 conventional medicines. The binding affinity of the ligands and standard drugs with each target protein were compared and analyzed. Additionally, only 9 substances with the lowest binding affinities were chosen for the ADMET study. Additionally, BIOVIA Discovery Studio Visualizer was used to visualize the top 3 ligands for each protein. Results: The two standard medications had higher binding affinities than the ligands after molecular docking, which revealed that Vitamin E and gamma-tocopherol were the ligands with the lowest binding affinities and were present in all three target proteins. Conclusion: The findings indicate that because vitamin E and gamma-tocopherol have lower binding affinities than standard drugs, they may one day be used to treat melanoma. The information provided here gives novel strategies for investigating the recommended ligands in vitro and in vivo, and if successful, for developing new melanoma inhibitors.
Keywords: ADMET analysis; BRAF; CDK2; Melanoma; c-KIT; molecular docking; phytocompounds